2018
DOI: 10.1063/1.5013252
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the cylindrical vacuum hohlraum energy in the first implosion experiment at the SGIII laser facility

Abstract: The cylindrical vacuum hohlraum energy at the SGIII laser facility [X. T. He and W. Y. Zhang, Eur. Phys. J. D 44, 227 (2007) and W. Zheng et al., High Power Laser Sci. Eng. 4, e21 (2016)] is investigated for the first time. The hohlraum size and the laser energy are intermediate between the Nova and NIF typical hohlraum experiments. It is found that the SGIII hohlraum exhibits an x-ray conversion efficiency of about 85%, which is more close to that of the NIF hohlraum. The LARED simulations of the SGIII hohlra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…In particular, the calculations become much lower than the experiments with the increase of time. The calculations with ERV show reasonable agreement with the measurements of all angles within the ±3% accuracy of the experimental observation [18,54,57]. It merits mentioning that the plasma filling has slight impact on the radiation temperature from the U42.…”
Section: Model Validation With Experimentssupporting
confidence: 78%
See 1 more Smart Citation
“…In particular, the calculations become much lower than the experiments with the increase of time. The calculations with ERV show reasonable agreement with the measurements of all angles within the ±3% accuracy of the experimental observation [18,54,57]. It merits mentioning that the plasma filling has slight impact on the radiation temperature from the U42.…”
Section: Model Validation With Experimentssupporting
confidence: 78%
“…The laser-to-x-ray conversion efficiency was calculated with a scaling equation h = t 0.8 , X ns 0.12 which is based on detailed numerical simulations [1,2,51]. This scaling law is applied to the case with a shot-length (no more than 3 ns) square pulse [12,[52][53][54]. With these two parameters and equations (2) and (3), the time-varying albedo and radiation temperature inside the hohlraum can be iteratively calculated, as drawn in figure 3.…”
Section: Model Validation With Experimentsmentioning
confidence: 99%
“…Furthermore, the CR should be lower than 25 to avoid the influence of the 270 nm-thick support tent [44, 45, and 50]. On the other hand, the CR should be greater than 16 to make the implosion performance more sensitive to driven asymmetry [46,48].…”
Section: Experimental Design and Numerical Simulation Codementioning
confidence: 99%
“…Its output lies in between the energy and power of the OMEGA and NIF facilities. A large amount of indirect-drive-implosion experimental work was performed to study the performance of implosions with convergences from 15 to 30 [46][47][48][49][50]. Previous work demonstrated that a square-pulse design with a lower convergence (∼15) achieved a higher implosion performance (the yield measured by 1D simulation (YOC 1D ) reached over 50%).…”
Section: Introductionmentioning
confidence: 99%
“…The hohlraum simulation was carried out with the 2D integrated code LARED-JC [27], and the comparison with the measured angular distribution of radiation flux was discussed elsewhere [24]. The capsule simulation was carried out with the 1D Lagrangian radiation hydrodynamic code RDMG [28].…”
Section: Comparison Between Experiments and Simulationsmentioning
confidence: 99%